Initial Clinical Impressions of the Critical Care of COVID-19 Patients in Seattle, New York City, and Chicago. (July 2020) - Sommer, Phillip; Lukovic, Elvedin; Fagley, Eliot; Long, Dustin R.; Sobol, Julia B.; Heller, Katherine; Moitra, Vivek K.; Pauldine, Ronald; O'Connor, Michael F.; Shahul, Sajid; Nunnally, Mark E.; Tung, Avery
Abstract : Since the first recognition of a cluster of novel respiratory viral infections in China in late December 2019, intensivists in the United States have watched with growing concern as infections with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus─now named coronavirus disease of 2019 (COVID-19)─have spread to hospitals in the United States. Because COVID-19 is extremely transmissible and can progress to a severe form of respiratory failure, the potential to overwhelm available critical care resources is high and critical care management of COVID-19 patients has been thrust into the spotlight. COVID-19 arrived in the United States in January and, as anticipated, has dramatically increased the usage of critical care resources. Three of the hardest-hit cities have been Seattle, New York City, and Chicago with a combined total of over 14, 000 cases as of March 23, 2020. In this special article, we describe initial clinical impressions of critical care of COVID-19 in these areas, with attention to clinical presentation, laboratory values, organ system effects, treatment strategies, and resource management. We highlight clinical observations that align with or differ from already published reports. These impressions represent only the early empiric experience of the authors and are not intended to serve as recommendations or guidelines for practice, but rather as a starting point for intensivists preparing to address COVID-19 when it arrives in their community.